Faktor-Faktor Yang Mempengaruhi Produktivitas Kerja Karyawan Pada PT. Scancom Indonesia di Semarang - Ledy Nevira Anggraini; Ira Setiawati; Rita Meiriyanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Problem factors that become obstacles in work productivity. The purpose of this study is to determine the effect of supervision, competence and work experience on work productivity at PT. Scancom New Zealand. The study sample was 156 respondents. The sampling technique used is saturated samples. The data analysis method uses multiple regression The results of the study found that there was a significant influence of supervisory variables on work productivity, there was a significant influence of competency variables on work productivity and there was a significant influence of work experience variables on work productivity. As well as the results of the test of the three independent variables on the dependent variables that there is a significant influence between the three variables on the independent variables silmultaneously (together). The results of the determination coefficient test obtained a value from the Adjusted R Square of 0.635 or 63.50% this can be interpreted to mean that Supervision, Competence and Work Experience can explain Work Productivity. While the remaining 36.50% was influenced by other variables that were not studied in this study.